HUBUNGAN KEJADIAN HIPERTENSI DENGAN PROTEIN URINE PADA IBU HAMIL TRIMESTER III DI RSUD dr. SOEDIRMAN KEBUMEN: THE CORRELATION BETWEEN THE INCIDENCE OF HYPERTENSION AND URINE PROTEIN IN THIRD TRIMESTER PREGNANT WOMEN AT RSUD dr. SOEDIRMAN KEBUMEN - Dwiar Apriyanti; Retno Sulistiyowati; Tantri Analisawati Sudarsono; Minto Rahaju (LPPM Universitas Abdurrab, 2024)
Abstract The prevalence of hypertension during pregnancy is 2.6 - 7.3% of all pregnancy incidents which can have risks for pregnant women, which is usually called the Maternal Mortality Rate (AKI). Hypertension during pregnancy is one of the causes of maternal death which can be detected early through a urine protein test. Urine protein is an important sign of preeclampsia which is caused by the kidney tubules not having optimal capacity to absorb protein. Based on research by Wulandari et al (2022) which states that there is a significant relationship between urine protein and blood pressure levels in TM III pregnant women at the Madukara I Banjarnegara Community Health Center with p=0.003. The aim of the study was to determine the relationship between the incidence of hypertension and urine protein in pregnant women in TM III at RSUD dr. Soedirman Kebumen. The research method used Observational Analytical through a Cross-Sectional design with a sample of 40 people, carried out in May - July 2023 at the Laboratory of RSUD dr. Soedirman Kebumen. Based on this research, a value of p=0.052 (p>0.05) was obtained, so it can be concluded that there is no significant relationship between the incidence of hypertension and urine protein in TM III pregnant women at Dr. Soedirman Hospital, Kebumen. Keywords: Hypertension, Third Trimester pregnant women, urine protein.